Avaliação do uso do elixir de pau d’arco (handroanthus impetiginosus (mart. Ex dc.) Mattos) na terapia complementar ao tratamento de neoplasias malígnas - Fortaleza, Francisca Teles (2023)
The WHO – World Health Organization – defines a medicinal plant as any plant that has substances that can be used for therapeutic purposes or that are precursors of semi-synthetic drugs. In South and North America, Ipê Roxo is explored in popular medicine as a herbal medicine with anticancer, antifungal, antibacterial and anti-inflammatory action. Studies have shown that the use of plants can stimulate cells and act as an alternative in the treatment of certain diseases, such as cancer. One of these alternatives is the use of the medicinal plant Pau D’Arco, also popularly known as Ipê Roxo. Lapachol is a naphthoquinone isolated from a natural source, the heartwood of trees of the ipê family, with a yield varying between 1 and 7% by mass, depending on the species and other factors such as region and seasonality. Currently, the treatment of cancers, for the most part, is considered one of the most challenging problems in medicine. The objective of the study was to evaluate the monitoring of the use of the Elixir of Pau D'arco (Handroanthus Avellanedae (Lorentz Ex Griseb) Mattos (Sin: Tabebuia Avellanedae Lorentz Ex Griseb) in complementary therapy to the treatment of neoplasms, produced and dispensed in the Phytotherapy Sector of the Coordination of Pharmaceutical Assistance Policies of the Secretary of Health of the State of Ceará. This is a basic, descriptive, documentary research based on secondary data with a qualitative and quantitative approach. The study had as its theme the analysis of records of patients with various types of malignant neoplasm that made use of the Elixir of Pau D`Arco dispensed by the Phytotherapy sector/COPAS/SESA between the months of March 2016 to March 2020. A survey was carried out in loco in that sector, where the sources that were analyzed, clinical records of patients diagnosed with malignant neoplasms using Elixir de Pau D`arco. patients. The sociodemographic characteristics of the patients were mostly Female 131 57.9%, Male 95 42.1% and Average Age 56 years. Despite not having enough information about what the purple Ipê causes as a benefit written on the cards, the patients reported a significant improvement with the use of this elixir. The use of medicinal plants as an alternative treatment along with cancer treatment has been gaining strength over time. Some studies already show the effectiveness of using complementary treatment practices, either directly to combat cancer or as a treatment for the consequences of cancer. Therefore, studies on alternative complementary medicine have been shown to be important for the treatment of various diseases, such as cancer. The results of the studies suggest that some medicinal plants, such as ipê-roxo, have metabolites that may have an inhibitory effect on the proliferation of cancer cells. In addition, they can also act as anti-inflammatory, antioxidant, anti-aging and anti-allergic agents. Diterpene alkaloids extracted from medicinal plants, such as Taxol, have also been used in the treatment of various types of cancer. These results demonstrate the importance of using complementary and alternative medicine in the treatment of diseases, such as cancer. Pau'Darco. It is necessary that primary studies are carried out to increase the level of scientific evidence regarding the use of medicinal plants to fight cancer.